Upaya Meningkatkan Hasil Belajar Siswa melalui Model Pembelajaran Inkuiri pada Mata Pelajaran Produk Kreatif dan Kewirausahaan di SMK Negeri 1 Gabuswetan - Sura Wijaya (Jurnal Pendidikan Madrasah, 2023)
The success of the teaching and learning process in the classroom is largely determined by the learning strategy, however complete and clear other components, without being implemented through the right strategy, these components will have no meaning in the process of achieving goals. Therefore, in Teaching and Learning Activities (KBM), teachers are required to apply certain strategies or methods in the implementation of learning. This research uses action research carried out in three cycles which include four stages, namely: design, activities and observations, reflection, and reference. The subject of the study was a student of grade XII Accounting A SMK Negeri 1 Gabuswetan for the 2020/2021 academic year. The data obtained are in the form of formative test results and observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning outcomes increased from cycle I to cycle III, namely, cycle I by 78.74%, cycle II by 80.40%, cycle III by 83.18%. The conclusion of this study is that the inquiry learning model can have a positive effect on the activities and learning outcomes of Class XII AKL A SMKN 1 Gabuswetan students, and this learning model can be used as an alternative learning for Creative Entrepreneurial Products.